2018
DOI: 10.1007/s00334-018-0686-7
|View full text |Cite
|
Sign up to set email alerts
|

Dung fungi as a proxy for megaherbivores: opportunities and limitations for archaeological applications

Abstract: The use of spores of coprophilous fungi from sedimentary sequences as proxy evidence for large herbivore abundance has garnered pronounced attention and scrutiny over the past three decades. In response to the rapid rate at which new information is being discovered on this topic, this paper presents a brief review of the archaeological applications so far, and outlines opportunities and limitations of using Sporormiella as a proxy for herbivore abundance. Specific archaeological uses of this proxy include unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 99 publications
0
69
0
Order By: Relevance
“…There are multiple biotic and abiotic factors affecting the representation of dung fungal spores in lake sediments, not just the presence of large herbivores in the local catchment (Parker and Williams, 2011;Perrotti and van Asperen, 2018). One key factor is the poor dispersal capability of the spores, which normally occurs close to ground-level and within a few metres of the surface of the dung source.…”
Section: Factors Influencing the Presence Of Sporormiella Sporesmentioning
confidence: 99%
“…There are multiple biotic and abiotic factors affecting the representation of dung fungal spores in lake sediments, not just the presence of large herbivores in the local catchment (Parker and Williams, 2011;Perrotti and van Asperen, 2018). One key factor is the poor dispersal capability of the spores, which normally occurs close to ground-level and within a few metres of the surface of the dung source.…”
Section: Factors Influencing the Presence Of Sporormiella Sporesmentioning
confidence: 99%
“…For future investigations, uncertainty regarding Sporormiella zero-counts could be avoided by more strictly adhering to the guidelines set by Etienne and Jouffroy-Bapicot (2014) recommending high exotic marker counts, independently from pollen sum. We also found that, when Sordaria, another reliable indicator of megaherbivores (Baker et al, 2013;Perrotti and van Asperen, 2019) is counted, the number of samples with indicative spores (i.e., Sporormiella and/or Sordaria) is doubled (12 vs 25 samples of 48 total). Therefore, including other dung fungal spores such as Sordaria appears to be an effective additional measure to minimise the uncertainty associated with Sporormiella zero counts.…”
Section: Discussionmentioning
confidence: 59%
“…The results from this study raise some important considerations for assessing herbivore presence in palaeoecological landscapes. It is clear that a wider range of fungal types are informative when assessing past herbivore presence, rather than relying on one indicator taxon such as Sporomiella (Perrotti and Van Asperen 2019). However, even with a range of fungal spores the data presented here suggest that some levels of grazing in wetter meadows might not be detectable or may require painstaking searches for sparse fungal spores in quantities insufficient to draw robust conclusions from.…”
Section: Implications For Palaeoecologymentioning
confidence: 80%
“…Overall, the low influx of dung fungal spores in the traps show that a landscape can be densely populated by large herbivores that do not always leave a dung fungal spore signal that is strong enough to distinguish it from background deposition rates. The absence of dung fungal spores in palaeoecological samples may therefore be less informative than their presence (Raper and Bush 2009;Jones et al 2017;Perrotti and Van Asperen 2019). Although in some cases Sporormiella spore abundance alone may indicate herbivore presence and/or abundance, the low levels of Sporormiella spore recovery, from both the Chillingham pollen traps and the dung, underline the importance of analysing all dung fungal spore taxa encountered in a palaeoecological sample, rather than limiting the analysis to a single spore type (Johnson et al 2015;Baker et al 2016;Perrotti and Van Asperen 2019).…”
Section: Fungal Spore Production Deposition and Preservationmentioning
confidence: 99%
See 1 more Smart Citation